2018
DOI: 10.1177/1010539518768036
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Apparent Temperature on Cardiovascular Mortality Using a Distributed Lag Nonlinear Model Analysis: 2005 to 2014

Abstract: The relationship between apparent temperature and cardiovascular disease (CVD) mortality was studied in Rasht, Iran, from 2005 to 2014. The effects of apparent temperature on CVD mortality were investigated using the distributed lag nonlinear model. Data on all types of cardiovascular mortality cases according to the International Classification of Diseases were collected from the only cardiovascular hospital in Rasht, and the meteorological variables were obtained from Rasht Meteorological Center during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
3
17
2
Order By: Relevance
“…In general, this study found an acute and short-term effect for hot temperature followed by a harvesting effect and a delayed effect for cold temperature on cardiovascular mortality. Similar lag structures have been found in a study performed in Rasht city, Iran [10] and in other studies conducted in different countries [5,32,33].…”
Section: E P U B a H E A D O F P R I N Tsupporting
confidence: 88%
See 2 more Smart Citations
“…In general, this study found an acute and short-term effect for hot temperature followed by a harvesting effect and a delayed effect for cold temperature on cardiovascular mortality. Similar lag structures have been found in a study performed in Rasht city, Iran [10] and in other studies conducted in different countries [5,32,33].…”
Section: E P U B a H E A D O F P R I N Tsupporting
confidence: 88%
“…In addition to temperature, air pollutants are well-known to have an effect on cardiovascular and respiratory mortality and can act as confounders or effect modifiers in the temperature-mortality relationship [9]. However, in some studies they have been ignored [10][11][12] or considered only as a confounder [13]. Regarding the simultaneous exposure to ambient temperature and air pollution, one can expect to see the synergistic effects of these factors in human physiology [9], and the evaluation of the interaction (or effect modification) between temperature and air pollution is of great importance, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Madrigano et al, 2013) found that there was a 36% increase in the USA (Samuel and Devi, 2015). The previous study by (Moghadamnia et al, 2005) conducted that risk of cardiovascular mortality is increased due to cold exposure (Iyer et al, 2019). NAFLD is an increasingly prevalent condition leading to an increased mortality rate (Choudhari and Jothipriya, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The four key sectors that will be affected by climate change are water, food, settlement and health. The heat-related mortality is the most direct health impact of global warming 2. Although well-studied investigations about the effect of hot temperature on acute coronary syndrome (ACS) in developed countries have been conducted,3 there is a paucity of research on this problem in low-income and middle-income countries such as Iran 4.…”
Section: Introductionmentioning
confidence: 99%